1987
DOI: 10.1093/oxfordjournals.aje.a114686
|View full text |Cite
|
Sign up to set email alerts
|

A Waterborne Outbreak of Leptospirosis

Abstract: During the period from July 10-26, 1984, 33 cases of serologically confirmed leptospirosis occurred in a small town in central Italy. The fatality rate, including the deaths of two unconfirmed cases, was 8.6% (3 of 35). Based on serologic evidence, the infection was caused by leptospires of the serogroup Australis. Epidemiologic study showed that the patients contracted the infection by drinking water from a fountain. The source of leptospiral contamination was probably a hedgehog trapped in a reservoir of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 0 publications
5
28
0
2
Order By: Relevance
“…[17][18][19] Serogroup Australis has been described in cattle, sheep, rats, donkeys, dogs, and hedgehogs. [20][21][22][23][24][25][26][27] Serogroup Autumnalis has been described in cattle, rats, mice, sheep, pigs, goats, and dogs. 3,17,20,22 On the basis of the most common reactive serogroups in the study population, likely local reservoirs include livestock, rodents, dogs, and potentially hedgehogs.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Serogroup Australis has been described in cattle, sheep, rats, donkeys, dogs, and hedgehogs. [20][21][22][23][24][25][26][27] Serogroup Autumnalis has been described in cattle, rats, mice, sheep, pigs, goats, and dogs. 3,17,20,22 On the basis of the most common reactive serogroups in the study population, likely local reservoirs include livestock, rodents, dogs, and potentially hedgehogs.…”
Section: Discussionmentioning
confidence: 99%
“…21 As illustrated by the triathlon in Illinois, the multisport races in Malaysian Borneo and Florida, this current study in Martinique, and several other outbreaks of leptospirosis associated with water; the first steps of prevention in athletes should be to avoid swimming in rivers, swallowing lake or river water, and prevent dermal cuts. 3,4,7,8,22,23 In addition, several studies suggest that doxycycline could be used either as chemoprophylaxis or as post-exposure prophylaxis and post-exposure empirical treatment. 21,[24][25][26][27] Both a study of U.S. Army soldiers who participated in a 3-week training exercise in the jungles of Panama and another study in residents of a rural area of the Andaman Islands found preventive efficacy of doxycycline, administered 200 mg once weekly.…”
Section: Discussionmentioning
confidence: 99%
“…Excepcionalmente, se ha comunicado ocurrencia de un brote asociado a la ingestión de agua procedente de una fuente contaminada 12 . Publicaciones recientes 1,4 destacan una disminución del riesgo ocupacional y aumento relativo del riesgo recreacional relacionado, especialmente, a baño en aguas estancadas u otras actividades asociadas a turismo aventura durante el período estival.…”
Section: Epidemiologíaunclassified
“…La bacteria penetra, principalmente, por inoculación a través de piel erosionada, mucosas nasofaríngea, bucal, genital, o conjuntival 1,2,4,20,21,24 . Excepcionalmente, se ha documentado transmisión sexual y transplacentaria 3 y la infestación por ingestión de agua contaminada 12 . Para ello, las leptospiras cuentan con propiedades agresivas, como su motilidad y, probablemente, el efecto de toxinas y/o enzimas del tipo fosfolipasas, que no han sido claramente definidas.…”
Section: Patogeniaunclassified